The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Handbook of Maize
DOI: 10.1007/978-0-387-77863-1_16
|View full text |Cite
|
Sign up to set email alerts
|

Helitrons: Their Impact on Maize Genome Evolution and Diversity

Abstract: Abstract.Gene movement by the newly-described Helitron family of transposable elements apparently has significantly impacted the evolution of this genome and has contributed to the lack of intra-specific gene collinearity between different maize inbred lines. The abundance of these elements and the extent of diversity among them remain largely undetermined. Several hypotheses have been proposed to explain their transposition and mechanism by which these elements prolifically capture and mobilize gene sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…These termini have been used to search for other family members in the maize genome database (Gupta et al 2005;Lal et al 2008). Using similar methodologies, we discovered a 50bp region spanning positions 1161-1211 of a genomic clone (gi: 21842135) that was nearly identical to the 5 0 termini of the Helitron insertions in sh2-7527 and ba1-ref (Lal et al 2003;Gupta et al 2005).…”
Section: Maize Cyp72a27-zm Represents a Cytochrome P450 Monooxygenasementioning
confidence: 98%
See 1 more Smart Citation
“…These termini have been used to search for other family members in the maize genome database (Gupta et al 2005;Lal et al 2008). Using similar methodologies, we discovered a 50bp region spanning positions 1161-1211 of a genomic clone (gi: 21842135) that was nearly identical to the 5 0 termini of the Helitron insertions in sh2-7527 and ba1-ref (Lal et al 2003;Gupta et al 2005).…”
Section: Maize Cyp72a27-zm Represents a Cytochrome P450 Monooxygenasementioning
confidence: 98%
“…The clones displaying both termini of either mutant insertion were further perused for Helitrons (Lal et al, 2008). The intervening sequence between the termini was considered a Helitron insertion.…”
Section: Database Searchesmentioning
confidence: 99%
“…The first examples of de novo Helitron insertions were isolated from two maize mutants (46, 73). Helitrons contribute substantially to a lack of colinearity in locus alignments across maize inbred lines (72). Gene annotation differences at the bz locus between two inbred maize lines reflect fragments captured/transduced by two Helitron transposons (124) (Figure 3 h ).…”
Section: Distribution Of Recent Transposon Activitymentioning
confidence: 99%
“…The majority of the elements identified thus far represent nonautonomous Helitrons containing chimeric segments derived from multiple genes although the analysis of the complete sequencing of one single maize inbred line provides only biased information of the extent and diversity of gene capture, transposition, and amplification by Helitrons [112]. In addition to Helitron, the Mutator superfamily possesses non-autonomous elements, called Pack-MULES, that have the ability to capture segments of nuclear gene(s) which can be arranged in chimeras [113,114]. Further, molecular evidence has revealed that these novel chimeras can be both transcribed and translated, which suggest that this mechanism of gene fragment capture inside of non-autonomous elements can produce, and evolve into, novel protein coding sequences [113,114].…”
Section: Transposons and Genetic Colinearitymentioning
confidence: 99%
“…In addition to Helitron, the Mutator superfamily possesses non-autonomous elements, called Pack-MULES, that have the ability to capture segments of nuclear gene(s) which can be arranged in chimeras [113,114]. Further, molecular evidence has revealed that these novel chimeras can be both transcribed and translated, which suggest that this mechanism of gene fragment capture inside of non-autonomous elements can produce, and evolve into, novel protein coding sequences [113,114]. Much like the Helitron elements, Pack-MULE transposition and amplification can lead to deviations in intraspecific synteny, and recent research has shown that Pack-MULEs preferentially capture GC-rich genomic segments and displayed biased insertion into the 5 end of coding regions [115].…”
Section: Transposons and Genetic Colinearitymentioning
confidence: 99%